2016
DOI: 10.7589/2015-02-047
|View full text |Cite
|
Sign up to set email alerts
|

DEVELOPMENT OF REFERENCE RANGES FOR PLASMA TOTAL CHOLINESTERASE AND BRAIN ACETYLCHOLINESTERASE ACTIVITY IN FREE-RANGING CARNABY'S BLACK-COCKATOOS (CALYPTORHYNCHUS LATIROSTRIS)

Abstract: Published avian reference ranges for plasma cholinesterase (ChE) and brain acetylcholinesterase (AChE) are numerous. However, a consistently reported recommendation is the need for species-and laboratory-specific reference ranges because of variables, including assay methods, sample storage conditions, season, and bird sex, age, and physiologic status. We developed normal reference ranges for brain AChE and plasma total ChE (tChE) activity for Carnaby's Black-Cockatoos (Calyptorhynchus latirostris) using a sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 23 publications
(32 reference statements)
0
1
0
Order By: Relevance
“…We found no differences between males and females, or between juveniles and adults (Figure A and B), in the species we were able to evaluate. Sex, age, and physiological and reproductive status have been suggested as causes of biological variability in human, rodent, and domestic animal plasma ChE activity (Tecles and Cerón ; Vaughan‐Higgins et al ). In birds, it has been reported that different sexes and ages differ in their enzymatic biochemistry and physiological activity (Maul and Farris ; Roy ; Norte et al ), but this issue is not well defined; other studies like ours found no differences (Zwarg et al ).…”
Section: Discussionmentioning
confidence: 99%
“…We found no differences between males and females, or between juveniles and adults (Figure A and B), in the species we were able to evaluate. Sex, age, and physiological and reproductive status have been suggested as causes of biological variability in human, rodent, and domestic animal plasma ChE activity (Tecles and Cerón ; Vaughan‐Higgins et al ). In birds, it has been reported that different sexes and ages differ in their enzymatic biochemistry and physiological activity (Maul and Farris ; Roy ; Norte et al ), but this issue is not well defined; other studies like ours found no differences (Zwarg et al ).…”
Section: Discussionmentioning
confidence: 99%